Eliot Freidson: progression and constraints in the biography of an intellectual Eliot Freidson: progressão e condicionamentos na biografia de um intelectual - André Pereira Neto (História, Ciências, Saúde: Manguinhos)
Eliot Freidson (1923-2005) is considered one of the founders of the sociology of medicine. Both his critics and admirers in the sociological and medical fields recognize his work as an international benchmark. This paper analyzes Freidson's intellectual biography without concentrating on his ideas or their transformation over the course of time. The emphasis is on the personal constraints that marked his intellectual career within a broader context, with the many different opportunities and choices. It establishes the intersection between the singular trajectory of an intellectual, and the structures, processes and events in which he was immersed and which he changed by his actions. Eliot Freidson (1923-2005) é considerado um dos fundadores da sociologia médica. Seus críticos e admiradores no campo médico e sociológico reconhecem que sua obra é de referência internacional. Este artigo analisa a biografia intelectual de Eliot Freidson (1923-2005), enfatizando não suas ideias e sua transformação ao longo do tempo, mas sim os constrangimentos particulares de sua carreira intelectual, inscritos em um amplo contexto, com diferentes oportunidades e escolhas. Estabelece a interseção entre a trajetória singular de um intelectual e as estruturas, processos e eventos nos quais ele estava imerso e que mudou com suas ações.